2021
DOI: 10.1016/j.dcn.2021.100950
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin promotes prosocial behavior and related neural responses in infant macaques at-risk for compromised social development

Abstract: Although positive effects of oxytocin (OT) on social functioning are well-demonstrated, little is known about the mechanisms through which OT may drive early social development, or its therapeutic efficacy in infancy. To address these critical issues, we investigated the effects of exogenous OT on neural (EEG) and behavioral responses during observation of live facial gestures in infant macaques with limited social exposure (i.e. nursery-reared). Three key findings were revealed. First, OT increased alpha supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Many studies 59 61 have demonstrated a connection between Oxytocin and social behavior, but the exact role of the two Oxytocin receptors in development and maintenance of social behavior remained to be clarified. Our data indicate that preference for companions develops gradually in wild-type zebrafish in the first few weeks, reaching a maximum social preference at 4 wpf, which is then maintained at a high level until at least 8 wpf.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies 59 61 have demonstrated a connection between Oxytocin and social behavior, but the exact role of the two Oxytocin receptors in development and maintenance of social behavior remained to be clarified. Our data indicate that preference for companions develops gradually in wild-type zebrafish in the first few weeks, reaching a maximum social preference at 4 wpf, which is then maintained at a high level until at least 8 wpf.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [37][38][39] have demonstrated a connection between Oxytocin and social behavior, but the exact role of the two Oxytocin receptors in development and maintenance of social behavior remained to be clarified. Our data revealed that preference for companions develops gradually in wild-type zebrafish in the first few weeks, reaching a maximum social preference at 4 wpf, which is then maintained at a high level until at least 8 wpf.…”
Section: Discussionmentioning
confidence: 99%
“…Central OT (COT) is synthesized in the hypothalamus and released into circulation by the neurohypophysis, which plays a significant role in milk excretion and uterine contraction at childbearing age ( Ferreira et al, 2019 ). Although it can increase trust, motivate social participation and group preference, and relieve social stress response as well as has anti-inflammation effects, there is no synthetic metabolic impact on bones ( Breuil et al, 2011 ; Hood et al, 2020 ; Sindermann et al, 2020 ; Festante et al, 2021 ). The evidence suggests that the injection of OT into the lateral ventricle has no effect on OB and OC formation as well as sero-bone conversion markers ( Tamma et al, 2009 ).…”
Section: Central Ot and Peripheral Otmentioning
confidence: 99%